2004
DOI: 10.1080/01490400490432064
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital in the Lived Experiences of Community Gardeners

Abstract: In this narrative inquiry, I explored a community garden as a social context in which social capital was produced, accessed, and used by a social network of community gardeners. In particular, I focused on the distribution of social capital among members of the garden group. My findings suggest social capital can be both a benefit and cost, depending upon the position a social actor occupies within a functioning social network. Based upon this finding, I encourage leisure researchers to critically analyze soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
174
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(184 citation statements)
references
References 34 publications
9
174
0
1
Order By: Relevance
“…Studies have explored which operational structures of AFNs enhance interactions among the participating individuals (Kurtz, 2001;Macias, 2008) and how a sense of community is experienced by community gardeners, CSA members, or farmers market patrons (Glover, 2004;Ostrom, 2007;Saldivar-Tanaka & Krasny, 2004). Other studies have investigated the extent to which community engagement motivates AFN participants to become socially active (Cox, Holloway, Venn, Dowler, Hein, Kneafsey, & Tuomainen, 2008) or how the social impact of AFN activities may extend beyond gardening or distributing food and enable mobilization toward other social issues faced by the community (Armstrong, 2000;Nettle, 2014;Ohmer, Meadowcroft, Freed, & Lewis, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have explored which operational structures of AFNs enhance interactions among the participating individuals (Kurtz, 2001;Macias, 2008) and how a sense of community is experienced by community gardeners, CSA members, or farmers market patrons (Glover, 2004;Ostrom, 2007;Saldivar-Tanaka & Krasny, 2004). Other studies have investigated the extent to which community engagement motivates AFN participants to become socially active (Cox, Holloway, Venn, Dowler, Hein, Kneafsey, & Tuomainen, 2008) or how the social impact of AFN activities may extend beyond gardening or distributing food and enable mobilization toward other social issues faced by the community (Armstrong, 2000;Nettle, 2014;Ohmer, Meadowcroft, Freed, & Lewis, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Or is there inequality in the social capital as a result of its distribution? In his own research, Glover (2004) found that there was inequity in the distribution of social capital amongst the members of the community garden as a result of their advantaged or disadvantaged structural positions. The very fact that higher SES schools in my study had active parent bodies involved suggests that these projects would necessarily have more access to the social capital (and other forms of capital) necessary to develop a successful project.…”
Section: Discussionmentioning
confidence: 99%
“…These findings beg me to consider the works of researchers who study issues related to social capital. Glover (2004), for example, explored if and how community gardens are "a social context in which social capital is produced, accessed, and used by a social network of community gardeners" (p. 143). Perhaps such an exploration is warranted in terms of school ground greening initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Una muestra de esta teoría podemos encontrarla en investigaciones en las que se informa acerca de cómo la participación en actividades de restauración y habilitación de zonas comunes del vecindario y jardines comunitarios mejora la percepción sobre el nivel de capital social de los miembros de la comunidad en los sujetos que se involucran en dichas actividades, en comparación con aquellos que no lo hacen (Alaimo et al, 2010;Glover, 2004;Glover, Parry y Shinew, 2005). Este resultado avala la idea de que existe conexión entre la participación en actividades comunitarias y la formación de capital social.…”
Section: Participación Comunitariaunclassified